5E Learning Cycle Debate Model Improves Scientific Argumentation Skills: Model Debat Siklus Pembelajaran 5E Meningkatkan Keterampilan Berargumen Ilmiah - Janatul Firdausi Nuzula; Noly Shofiyah (Academia Open, 2025)
General Background: Scientific argumentation skills are essential competencies in twenty-first-century science education, integrating communication and critical thinking abilities required for informed decision-making. Specific Background: However, junior high school students often struggle to construct evidence-based arguments, as many can state claims but fail to provide supporting data, warrants, or rebuttals. Knowledge Gap: Despite the recognized value of student-centered models, limited empirical evidence exists regarding the integration of the 5E Learning Cycle with structured classroom debate to address low argumentation performance. Aims: This study aims to analyze the application of the 5E Learning Cycle model integrated with the debate method on students’ scientific argumentation skills in junior high school science. Results: Using a quantitative one-group pretest-posttest design with 96 students, findings revealed substantial score increases across three classes, with N-Gain values of 0.83 and 0.80 (high) and 0.68 (moderate); paired t-tests showed significant pretest–posttest differences (p < 0.05), and one-way ANOVA indicated significant variation among classes (p = 0.039). Novelty: The study demonstrates that embedding structured debate within the explanation phase of the 5E cycle provides a systematic approach to fostering evidence-based reasoning and multidimensional argument construction. Implications: These findings suggest that science teachers can adopt this integrated model to promote active participation, confidence in expressing ideas, and stronger scientific reasoning in classroom learning. Highlights: Students demonstrated marked gains in constructing evidence-supported claims across all observed groups. Statistical testing confirmed meaningful differences between initial and final assessments. Performance patterns varied among classes despite consistently positive progress. Keywords: 5E Learning Cycle; Debate Method; Scientific Argumentation; Science Education; Junior High School